KINERJA BENIH LELE YANG DIBERI PAKAN TAMBAHAN SERBUK SPIRULINA - Ria Putri Kusumaning Ayu; Pungky Slamet Wisnu Kusuma (FMIPA : Universitas PGRI Adi Buana, 2018)
Feed is an important element that can support the growth and survival of fish. Feed that is suitable for nutrition and high digestion value can support maximum growth in cultivated fish. S. plastensisis a type of cyanobacteria that contains nutrients such as proteins, essential fatty acids, minerals, vitamins, and antioxidants. This study aims to determine the effect of the addition S. plastensis powder in feed on the growth, SR and FCR of catfish seeds. Experimental study with 5 treatments and 5 replications, treatment A (S. plastensis powder 0 g / kg feed), treatment B (S. plastensis powder 2 g / kg feed), C treatment (S. plastensis powder 3 g / kg feed) and treatment D (S. plastensis powder 4 g / kg feed), and E treatment (S. plastensis powder 6 g / kg feed). Feed is given twice, every morning and evening for 35 days. The results showed the addition of S. plastensis powder to the feed could have a significant effect (P